Estimation of geomagnetic conjugate points by using Pc5 pulsations - Ken-ichi Kato; Yutaka Tonegawa; Natsuo Sato (National Institute of Polar Research, 1992)
In the present paper, we have attempted to estimate the geomagnetic conjugate points by the method of TONEGAWA and SATO using Pc5 geomagnetic pulsation data obtained simultaneously at three stations in Iceland and at three stations in Antarctica (including Syowa Station) during the period of March and May in 1988. It is assumed in the estimation that Pc5 pulsations are odd mode standing oscillations of the field line and have linear phase variations among the stations in the horizontal plane. The result shows that conjugate points of Syowa Station estimated from Pc5 events are concentrated around the point calculated from the magnetic field model of TSYGANENKO, within the range of ±3°in the longitude, i. e., less than 1/5 wave length, and ±0.5°in the latitude.